Analisis Perencanaan Perkerasan Lentur Pembangunan Ruas Jalan Kutabangun - Kutakendit Liang Melas Datas Kabupaten Karo - Ginting, Dandi (Politeknik Negeri Lhokseumawe, 2025)
Abstract. Karo Regency is located in North Sumatra Province, including large and crowded regencies. The population in Karo Regency has increased rapidly in recent years. Karo Regency is located in the highlands at an altitude of between 600 and 1,400 meters above sea level which is strategic for the agricultural sector. Infrastructure is very influential in the process of increasing the economy and access to activities in an area such as Karo Regency, especially on the Kutabangun-Kutakendit Road Section at the Pola Tebu Village point STA 0+000 - 2+000. This study aims to determine the condition of road infrastructure and Road Section Development Planning which is a nest of access for the surrounding community to market agricultural products. In this study, the flexible pavement thickness is planned using the 2017 revised Bina Marga Pavement Design Manual method and the 1993 AASHTO Pavement Design Manual Method. Land subsidence on the road body and the small existing road along the Kutabangun-Kutakendit Liang Melas Datas road is one of the factors that threatens the sustainability of the road function, land subsidence on the road body is generally triggered by natural factors such as high rainfall, geological conditions that are prone to landslides and non-scientific factors such as excavation activities at the foot of the slope and deforestation. Based on the results of the analysis and calculations, the results obtained in the 2017 Revised Highways Pavement Design Manual for the surface layer are 10 cm, the upper foundation layer is 40 cm, and the embankment is 17.5 cm, while in the 1993 AASHTO Pavement Design Manual Method, the surface layer is 11 cm thick, the upper foundation layer is 23 cm, the lower foundation layer is 26 cm and the embankment is 10 cm.